Meningkatkan Aktivitas dan Hasil Belajar Matematika Menggunakan Model PBL, GI dan ST - Dea Natasya Putri; Herti Prastitasari (CV.ITTC INDONESIA, 2025)
This study aims to describe the activities of teachers, analyze student activity during the learning process and analyze learning outcomes. The approach applied is qualitative and Class Action Research (PTK). Data analysis techniques were collected through observation sheets and written tests. The results showed that the first meeting teacher activity achieved a score of 22 increased until the fourth meeting with a score of 35. The activity of students at the first meeting reached 50% increased until the fourth meeting reached 100%. Learning outcomes cognitive and affective aspects of the first meeting achieved a 36% increase until the fourth meeting reached 100% and psychomotor aspects of the first meeting achieved a 39% increase in the fourth meeting reached 100%. With this it can be concluded that the use of PBL, GI and Snowball Throwing models can improve activity and learning outcomes. The advice for principals, teachers and other researchers is to be able to improve the quality of education, the quality of learning and as a reference in applying the learning model.